Antibody-mediated inhibition of Nogo-A signaling promotes neurite growth in PC-12 cells. (28th January 2016) - Yazdi, Iman K; Taghipour, Nima; Hmaidan, Sarah; Palomba, Roberto; Scaria, Shilpa; Munoz, Alvaro; Boone, Timothy B; Tasciotti, Ennio
The use of a monoclonal antibody to block the neurite outgrowth inhibitor Nogo-A has been of great interest for promoting axonal recovery as a treatment for spinal cord injury. While several cellular and non-cellular assays have been developed to quantify the bioactive effects of Nogo-A signaling, demand still exists for the development of a reliable approach to characterize the effectiveness of the anti-Nogo-A antibody. In this study, we developed and validated a novel cell-based approach to facilitate the biological quantification of a Nogo-A antibody using PC-12 cells as an in vitro neuronal cell model. Changes in the mRNA levels of the neuronal differentiation markers, growth-associated protein 43 and neurofilament light-polypeptide, suggest that activation of the Nogo-A pathway suppresses axonal growth and dendrite formation in the tested cell line. We found that application of anti-Nogo-A monoclonal antibody can significantly enhance the neuronal maturity of PC-12 cells by blocking the Nogo-A inhibitory effects, providing enhanced effects on neural maturity at the molecular level. No adverse effects were observed on cell viability.